2005
DOI: 10.1038/sj.bjc.6602553
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and pharmacokinetic study of the novel chemoprotector BNP7787 in combination with cisplatin and attempt to eliminate the hydration schedule

Abstract: BNP7787 (disodium 2,20 -dithio-bis-ethane sulphonate; Tavoceptt) is a novel agent developed to protect against cisplatin (cisdiammine-dichloroplatinum(II))-associated chronic toxicities. In this study, we determined the recommended dose of BNP7787 when preceding a fixed dose of cisplatin, the pharmacokinetics (PKs) and the possible reduction of saline hydration. Patients with advanced solid tumours received BNP7787 in escalating doses of 4.1 -41 g m À2 as a 15-min intravenous (i.v.) infusion followed by cispla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
(32 reference statements)
4
12
0
Order By: Relevance
“…BNP7787 pharmacokinetics was similar to those reported in a previous human phase I study [3, 21]. After cessation of infusion, the BNP7787 curves showed single-exponential decay (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…BNP7787 pharmacokinetics was similar to those reported in a previous human phase I study [3, 21]. After cessation of infusion, the BNP7787 curves showed single-exponential decay (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…We postulate that the formation of these mesnadisulfide heteroconjugates and free mesna at specific locations in vivo may contribute to BNP7787-mediated cisplatin nephroprotection (Fig. 8) [1][2][3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical and preclinical studies, BNP7787 (disodium 2,2 -dithio-bis ethane sulfonate; Tavocept TM ), a water-soluble disulfide, has been shown to have potential for protecting against cisplatininduced nephrotoxicity without reducing anti-tumor activity [1][2][3][4][5][6][7][8][9][10]. We have proposed that BNP7787-mediated nephroprotection involves the non-enzymatic thiol transfer reactions of BNP7787 with physiological thiols, such as glutathione, cysteine, homocysteine, cysteinyl-glutamate, or cysteinyl-glycine, present in plasma and in cells to produce active mesna-disulfide heteroconjugates that may impart nephroprotection ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in animal models, BNP7787 did not exhibit tumor protection when given with taxane and platinum agents and concurrently prevented lethal chemotherapy-induced toxicity from paclitaxel, cisplatin, carboplatin, and oxaliplatin (11,37,38,40,46). In phase I and III clinical trials, BNP7787 was not observed to interfere with the antitumor activity of cisplatin and paclitaxel (11,47). In an additional phase III clinical trial, treatment with BNP7787 seemed to significantly improve 1-year survival of patients with advanced primary adenocarcinoma of the lung who were being treated with cisplatin and paclitaxel regimens in the first-line setting (36).…”
Section: Discussionmentioning
confidence: 98%